1989
DOI: 10.1152/jappl.1989.67.4.1311
|View full text |Cite
|
Sign up to set email alerts
|

Cervical magnetic stimulation: a new painless method for bilateral phrenic nerve stimulation in conscious humans

Abstract: Assessing diaphragmatic contractility is a common goal in various situations. This assessment is mainly based on static or dynamic maximal voluntary maneuvers and twitch transdiaphragmatic pressures (Pdi) obtained by stimulation of the phrenic nerves (PS). PS eliminates the central components of diaphragmatic activation, but the available techniques of PS remain subject to some limitations. Transcutaneous PS is painful, and needle PS is potentially dangerous. Time-varying magnetic fields can stimulate nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
206
4
16

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(236 citation statements)
references
References 0 publications
10
206
4
16
Order By: Relevance
“…As noted by Luo et al (17), the PNCT values reported in earlier studies from our laboratory were longer (32,33). This is likely accounted for by the lower power of the stimulator used in these studies.…”
Section: Comparison With Previous Data From Our Laboratorymentioning
confidence: 51%
See 2 more Smart Citations
“…As noted by Luo et al (17), the PNCT values reported in earlier studies from our laboratory were longer (32,33). This is likely accounted for by the lower power of the stimulator used in these studies.…”
Section: Comparison With Previous Data From Our Laboratorymentioning
confidence: 51%
“…As in a previous study (35), the technique was slightly modified compared with its initial description (33,34) in that the subjects kept the neck in a neutral position instead of bending it forward. The handle of the coil was directed caudally and held either parallel to the vertebral column or at a 45°angle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with limb muscles, it is difficult to objectively assess fatigue of the diaphragm because both the muscle and the motor nerves are relatively inaccessible. Thus force development across the muscle (i.e., transdiaphragmatic pressure) is estimated by measuring the pressure difference between gastric and esophageal pressures induced by stimulation of both phrenic nerves (9,90,97,110). For the abdominal muscles, force output is estimated by measuring the gastric pressure response to magnetic stimulation of the thoracic nerve roots (61).…”
Section: Exercise-induced Respiratory Muscle Fatiguementioning
confidence: 99%
“…These findings and the methodological problems described above prohibit definitive conclusions and warrant further investigation using new techniques and different methodology. Magnetic stimulation of the phrenic nerves is an accepted alternative to electrical stimulation and is a nonvolitional, simple and reproducible technique of assessing inspiratory muscle function that reduces the difficulties encountered with electrical stimulation [10].…”
mentioning
confidence: 99%